Blocking Notch signal pathway delayed uric acid-induced renal injury in rats - Shen Yu-li; Pan Fu-lin; Fu Jun-zhou; Zhang Xin-zhou (Linchuang shenzangbing zazhi)
ObjectiveTo investigate the effect and mechanism of γ-secretase inhibitor DAPT on uric acid-induced renal injury in rats.MethodsTwenty-one male SD rats were randomly divided into normal control group （control， n=7）， hyperuricemia model group （OA+UA， n=7）， and DAPT treatment group （OA+UA+DAPT， n=7）. The OA+UA group was given 2.5 mL/100 g of 2% oxazine by gavage， 3 times a day， and 0.1 mmol/L uric acid was given to drink water at the same time. OA+UA+DAPT was given Notch signaling pathway specific inhibitor every day while modeling. γ-secretase inhibitor DAPT 500 μg/100 g intraperitoneal injection. The control group was given normal food and intraperitoneally injected with the same volume of normal saline. Seven rats in each group were sacrificed at 8 weeks after model establishment. The histopathological changes of the kidney were determined by hematoxylin-eosin staining （HE） and Masson staining. qRT-PCR and Western blot were used to detect the level of Notch signaling pathway receptor Notch1， ligand Jagged1 and hair division-related enhancer 1 （Hes1） ，TGF-β1 and α-SMA.The location of the above indicators in the kidneys of rats was observed by immunohistochemistry.ResultsCompared with the control group， HE staining in the OA+UA group showed that some renal tubular epithelial cells were swollen and shed .The lumens were expanded and deformed. Part of renal tubules were atrophied and widening. With inflammatory infiltration， the brown needle-like radial urate crystals can be seen in the renal interstitium at 8 weeks. Masson staining showed obvious wavy collagen fibers in the tubulointerstitium， which were bright green staining.While the morphological changes were milder in OA+UA+DAPT group.Compared with the control group，the expression levels of Notch1/Jagged1/Hes1， TGF-β1 and α-SMA were significantly increased in the OA+UA group. Compared with the model group， the damage of renal in the rats after DAPT treatment were significantly alleviated. The renal interstitial fibrosis was reduced，As same as the expression levels of Notch1/Jagged1/Hes1，the expression of TGF-β1 and α-SMA decreased in OA+UA+DAPT group.ConclusionsThe Notch signaling pathway is activated during uric acid-induced renal injury in rats. DAPT，the Notch signaling pathway inhibitor， would delay the renal injury in rats induced by uric acid.